A taxonomic revision of the neotropical termite genus Ruptitermes (Isoptera, Termitidae, Apicotermitinae) - Acioli, Agno Nonato Serrão; Constantino, Reginaldo (Zootaxa, 2015)
The taxonomy of Ruptitermes Mathews 1977 is revised. Nine new species are described: R. araujoi, sp. n. (from Brazil), R. atyra, sp. n. (from Brazil, Peru, and Panama), R. bandeirai, sp. n. (from Brazil), R. cangua, sp. n. (from Brazil), R. kaapora, sp. n. (from Paraguay and Brazil), R. krishnai, sp. n. (from Trinidad), R. maraca, sp. n. (from Brazil), R. piliceps, sp. n. (from Brazil), and R. pitan, sp. n. (from Brazil). Ruptitermes franciscoi (Snyder 1959), new combination, is transferred from Anoplotermes Fr. Müller to Ruptitermes. Ruptitermes proratus Emerson 1949 is placed under the synonymy of R. reconditus (Silvestri, 1901). The genus is redescribed to accommodate all the species included. Ruptitermes arboreus, R. reconditus and R. xanthochiton are redescribed based on the examination of large series. A key to the 13 species of the genus based on the external morphology of workers is provided. The enteric valve armature is described and illustrated for all species except R. kaapora. Distribution maps are presented for all species.